Effect of Roof and Diaphragm Connectivity on Dynamic Behaviour of the PP-band Retrofitted Adobe Masonry Structures - Sathiparan, N. (My University, 2018)
This paper discusses the shaking table test results of three PP-band (Polypropylene band) retrofitted quarter scale one-story masonry house models with different roof conditions. Better connections between masonry wall and roof connection are one factor to improve the seismic safety of the masonry houses. Past studies show that PP-band retrofitting improves the integrity of structural components and prevent the collapse of masonry structures during an earthquake. Although the effect of masonry unit type, surface plastering, the pitch of the PP-band mesh, PP-band connectivity in mesh and tightness of the mesh attachment to walls were studied by experiment program, the effect of the roof and its diaphragm connectivity on PP-band retrofitted masonry structure is nonexistent. Therefore, an experimental program was designed and executed for an understanding the effect of the roof and its connection on the dynamic behavior of the PP-band retrofitted box-shaped masonry house models. Results reveal that the PP-band retrofitted models with proper roof diaphragm improves the seismic behavior with respect to lateral drift, shear resistance and ductility.
Keywords: PP-band retrofitting; adobe masonry